Polyvocal Professional Learning through Self-Study Research
XIV, 266 p.
Keywords: "Polyvocal Professional Learning through Self-Study Research illustrates the power of “we” for innovative and authentic professional learning. The 33 contributors to this book include experienced and emerging self-study researchers, writing in collaboration, across multiple professions, academic disciplines, contexts, and continents. These authors have noted and reviewed each other’s chapters and adapted their contributions to generate a polyvocal conversation that significantly advances scholarship on professional learning through self-study research. Building on, and extending, the existing body of work on self-study research, the book offers an extensive and in-depth scholarly exploration of the how, why, and impact of professional learning through context-specific, practitioner-led inquiry. The chapters illustrate polyvocal professional learning as both phenomenon and method, with the original research that is presented in every chapter adding to the forms of methodological inventiveness that have been developed and documented within the self-study research community. “This unique book represents an inspiring step forward in self-study research. Authors from various continents provide evidence of how the “I” can be strengthened through the “we” perspective, showing convincingly how polyvocality, transdisciplinarity, and an intercultural approach deepen professional learning. This powerful book offers important new insights for the methodology of self-study, with an impact beyond teachers and teacher educators.” Fred A. J. Korthagen, Professor Emeritus at Utrecht University, The Netherlands “A fascinating set of chapters illustrate the importance of many lenses and many voices when studying one’s practice. Each chapter testifies that self-study and its ties to improvement through posing thoughtful questions, collecting and analyzing relevant data, and interrogating the interpretation of one’s analysis of self are global and cross-disciplinary. This book is a must-read!” Renée T. Clift, Professor and Associate Dean, University of Arizona, USA".